Euthanasia in Christian Ethic-Theological Context: Pros And Cons - David Ming; Benjamin Metekohy; Novita Loma Sahertian (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2021)
Science and technology are undergoing rapid development and progress. It is due to the increasing number of modern inventions. Among the technological discoveries that are very important are in the medical field. With modern medical equipment, the suffering of a patient can be reduced. But in reality, there are still some patients who have severe suffering. Patients who experience prolonged illness invites empathy from the family. To relieve his suffering, the family who could not bear to see his condition asked the doctor to take actions that could shorten the patient's life, this kind of action in the medical world is known as euthanasia. This study aims to find out how the study of active euthanasia in the view of Christian law. This study is a literature review using an ethical-theological approach by studying books and scientific works related to the discussed problem.